Kritik Sosial Teks ‘Hidup Ini Brengsek Dan Aku Dipaksa Menikmatinya’ Dalam Semiotika Roland Barthes - Alifia Arsya Nabela; Dwi Prasetyo (DIGICOM : Jurnal Komunikasi dan Media, 2022)
Social criticism is a means of communication in conveying an idea to create a social change. The research with the title Social Criticism in the Text "Life is Jerk and I'm Forced to Enjoy It" is motivated by the researcher's curiosity about social criticism contained in the text. The purpose of this research is to understand the meaning of signifier and signified, connotation, denotation and myth of social criticism contained in the text. This research uses the semiotic analysis method of Roland Barthes. And using the theory of social criticism which is divided into several aspects, namely: politics, economics, law, culture and defense and security. The results of data analysis from this study are, forms of criticism of various social problems and our attitude in responding to social problems that occur. The myth in the text "Life is a jerk and I am forced to enjoy it" is that apathy towards social problems that occur will only perpetuate these problems.